Is the hidden curriculum a relevant issue in educational processes (2004)
This paper explores some ideas about the hidden curriculum as an amount of ideas and beliefs which are implicit in an indirect way into the scholar life. Those ideas are regarding to gender equality, social status and racial difference, among others. We consider teachers are able to integrate the hidden curriculum as a pedagogical strategy in the classroom. Examples of integration include activities such as observation techniques, role-plays, peer modeling and particularly, the portfolio as a useful tool for reflection which reveals the hidden curriculum. Key words: Hidden Curriculum, Pedagogical Strategy, Portfolio, ELT Processes, Stereotypes Este documento explora algunas ideas acerca del currículo oculto como una suma de ideas y creencias que están implícitos de una forma indirecta dentro de la vida escolar. Estas ideas están relacionadas con la equidad de género, diferencias sociales y raciales, entre otros. Consideramos que es posible para los docentes integrar el currículo como estrategia pedagógica en el aula. Ejemplos de esta integración incluyen técnicas de observación, juegos de roles, modelamiento en parejas y particularmente, el portafolio como herramienta de reflexión que permita hacer evidente el currículo oculto. Palabras claves: Currículo Oculto, Estrategia Pedagógica, Estereotipos, Enseñanza de Inglés, Portafolio